Public Debt and the Political Economy of Reforms - Pierre C. Boyer; Christoph Esslinger; Brian Roberson (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We develop a two-period model of redistributive politics in which two politicians compete in an election in each period. In the first period, the politicians propose both whether to experiment with an efficient reform with uncertain benefits and choose the amount of public debt. Politicians also allocate pork-barrel spending to voters in each period. We show that allowing politicians to raise debt ensures that the reform is always implemented when the reform's ratio of private good to public good gains exceeds a threshold, i.e. the reform generates enough private good benefits. This is not the case when the reform's ratio of private good to public good gains is below this threshold. We also examine hard and a soft debt limits, and find that both limits reduce the political success of the reform. However, at moderate debt levels soft limits dominate hard limits with respect to equilibrium efficiency of reform provision.
Keywords: C72; D72; D78; H60; 330; political competition; public debt; reforms; redistributive politics; debt and spending limits